2015
DOI: 10.1128/jvi.01742-15
|View full text |Cite
|
Sign up to set email alerts
|

Transition toward Human Cytomegalovirus Susceptibility in Early Human Embryonic Stem Cell-Derived Neural Precursors

Abstract: Congenital human cytomegalovirus (HCMV) infection is associated with neurodevelopmental disabilities. To dissect the earliest events of infection in the developing human brain, we studied HCMV infection during controlled differentiation of human embryonic stem cells (hESC) into neural precursors. We traced a transition from viral restriction in hESC, mediated by a block in viral binding, toward HCMV susceptibility in early hESC-derived neural precursors. We further revealed the role of plateletderived growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
(60 reference statements)
3
20
0
Order By: Relevance
“…Fortunately, large populations of almost pure cell types can be generated using either embryonic stem (ES) cell or induced pluripotent stem cell (iPSC) technologies. Interestingly, NPCs derived from 10-week gestation tissue were substantially more permissive to infection (30) than either ES-or iPS-derived NPCs (31)(32)(33)(34)(35)(36)(37)(38); also our unpublished results). This suggests that the more primitive stage of development of the ES-and iPS-derived cells influences their interactions with the virus.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Fortunately, large populations of almost pure cell types can be generated using either embryonic stem (ES) cell or induced pluripotent stem cell (iPSC) technologies. Interestingly, NPCs derived from 10-week gestation tissue were substantially more permissive to infection (30) than either ES-or iPS-derived NPCs (31)(32)(33)(34)(35)(36)(37)(38); also our unpublished results). This suggests that the more primitive stage of development of the ES-and iPS-derived cells influences their interactions with the virus.…”
mentioning
confidence: 52%
“…All of the infection studies performed to date on undifferentiated ES or iPS cells (including ours described herein) find both cell types to be essentially nonpermissive for infection, as measured by de novo expression of immediate early (IE) antigens (Ags) (31,33,35,37). However, the susceptibility to infection of these cells is much less clear.…”
mentioning
confidence: 96%
“…This notion of a gradual release of viral restriction blocks along neuronal differentiation was corroborated by the transition to an increased susceptibility to HCMV during neural differentiation of ESCs into neural spheres [103]. Susceptibility to HCMV appeared to be correlated to expression of the platelet-derived growth factor receptor alpha (PDGFRα) [103]. Brown et al showed correspondingly a lack of permissiveness of iPSCs to HCMV, but also identified iPSCs to be susceptible to HCMV infection through positive staining for the input tegument proteins [104].…”
Section: The Infection Of Pluripotent Stem Cell-based Models Of Humanmentioning
confidence: 87%
“…Due to their similarity to cells in the developing neural tube, they are suggestive of the presence of a cellular harbor at a very primitive neuronal developmental stage for virus persistence along further neuronal differentiation stages [101]. This notion of a gradual release of viral restriction blocks along neuronal differentiation was corroborated by the transition to an increased susceptibility to HCMV during neural differentiation of ESCs into neural spheres [103]. Susceptibility to HCMV appeared to be correlated to expression of the platelet-derived growth factor receptor alpha (PDGFRα) [103].…”
Section: The Infection Of Pluripotent Stem Cell-based Models Of Humanmentioning
confidence: 89%
“…Progenitors of the myeloid lineage are hosts for latent HCMV, and differentiation to macrophages or dendritic cells results in reactivation of the virus. Recently, Berger et al investigated the transition from restriction of HCMV infection in human embryonic stem cells (hESC) toward susceptibility in hESC-derived neural precursors [36]. Using protocols for controlled induction of differentiation of hESC into neural precursors, they discovered PDGFR-/ as a determinant of HCMV susceptibility.…”
Section: Cell Differentiationmentioning
confidence: 99%